2018
DOI: 10.1016/j.bbadis.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of biliary injury and altered bile acid metabolism

Abstract: In the last 25 years, a number of animal models, mainly rodents, have been generated with the goal to mimic cholestatic liver injuries and, thus, to provide in vivo tools to investigate the mechanisms of biliary repair and, eventually, to test the efficacy of innovative treatments. Despite fundamental limitations applying to these models, such as the distinct immune system and the different metabolism regulating liver homeostasis in rodents when compared to humans, multiple approaches, such as surgery (bile du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 112 publications
2
102
0
1
Order By: Relevance
“…C). Prior studies revealed co‐IF of CK19 and desmin of ductular structures within the portal field . We found high labeling efficiency of desmin + periportal mesenchymal cells in DRs.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…C). Prior studies revealed co‐IF of CK19 and desmin of ductular structures within the portal field . We found high labeling efficiency of desmin + periportal mesenchymal cells in DRs.…”
Section: Resultssupporting
confidence: 61%
“…Prior studies revealed co-IF of CK19 and desmin of ductular structures within the portal field. (24) We found high labeling efficiency of desmin + periportal mesenchymal cells in DRs. Colabeling with α-smooth muscle action (α-SMA) also failed to detect the presence of H19RNA in α-SMA + cells (not shown).…”
Section: H19rna Is Identified In F4/80 + Kupffer Cells In the Bdl Moumentioning
confidence: 58%
See 2 more Smart Citations
“…PBC and PSC are complex diseases with multiple pathogenic mechanisms activated . To evaluate the influence of the cholestatic component in Areg expression, we used two models of cholestatic liver injury of extra‐ or intrahepatic origin, BDL, and ANIT administration, respectively . Areg mRNA was strongly up‐regulated and AREG protein was detected in cholangiocytes and hepatocytes at 5 days post‐BDL, which corresponds to the peak of hepatic regenerative response (Fig.…”
Section: Resultsmentioning
confidence: 99%